When it all fails—use the iliac crest - Daner III, William E.; Chang, Michelle J.; Fox, Henry M.; Higgins, Laurence D.; Warner, Jon J. P. (Annals of Joint, 2017)
Traumatic anterior glenohumeral dislocation is a common injury, particular in young and active patients. Depending on the severity of the injury and patient-specific factors, a soft tissue Bankart repair or a procedure to address bone loss may be elected. Herein we discuss indications for performing a reconstruction using autogenous tricortical iliac crest bone graft (ICBG), the Eden-Hybinette procedure. Operative planning, technique, and post-operative care are described. With proper technique, this methodology can address sizable glenoid defects. In the subset of instability patients in which the Latarjet fails, the Eden-Hybinette procedure has been shown in the literature to be a reliable option for restoring stability.